2022
DOI: 10.1097/prs.0000000000008908
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Predictors of Successful Replantation of Distal Digits at the Nail Bed Level: The Contribution of Digital Nerve Repair to Survival Rate

Abstract: Background: Replantation of amputated digits at the nail bed level is surgically challenging and differs from replantation at a more proximal amputation level. This study aimed to determine the predictors influencing the success rate of fingertip replantation. Methods: Overall, 239 digits of 226 patients who underwent replantation surgery from August of 2009 to March of 2020 were considered. A total of 15 independent variables (i.e., sex; age; injured hand; digit; history of smoking; history of hypertension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Recent studies have suggested that the success rate is similar between replantation/revascularization with and without vein graft. [4][5][6][7][8][9] However, the success rate of replantation/revascularization using interpositional vein graft may be improved if difficult cases are avoided.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have suggested that the success rate is similar between replantation/revascularization with and without vein graft. [4][5][6][7][8][9] However, the success rate of replantation/revascularization using interpositional vein graft may be improved if difficult cases are avoided.…”
Section: Discussionmentioning
confidence: 99%
“…The success rate of replantation/revascularization varies between studies and depends on the surgeon's technique and wide-ranging indications in difficult cases. [1][2][3][4][5] A vein graft is more readily used in crush and avulsion amputations compared with guillotine amputations. 6 According to recent reports, there is no difference in the success rate between vein graft and non-vein graft groups.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations